Nilai Sosial Masyarakat Samin di Desa Larikrejo Undaan Kudus - Suryanto, Halim; Faizah, Nurul; Setiyawati, Heny Septyan; Yulia putri, Rizqi Dian; Kanzunnudin, Mohammad (Pustaka : Jurnal Ilmu-Ilmu Budaya, 2023)
This study discusses the social values ??of the Samin people in the village of Larikrejo which aims to (1) find out the factors that cause the Samin people to stick to their values ??and traditions, (2) find out the social values ??of the Samin tribe and (3) find out the values ??and the traditions of the Samin people in terms of everyday life. In this study, researchers used ethnographic research methods. The ethnographic method is a method used to describe things related to the Samin community in depth. In this study, it shows that social values ??between the Samin people and the surrounding community are in the form of cooperation and interaction, this form of interaction, both the Samin tribe and the community in general, often cooperate in terms of mutual cooperation between members of the community, for example mutual cooperation in building residents' houses in splice system. In social interaction between the Samin community and the surrounding community, it is influenced by several factors, namely the social situation, the power of group norms, personal goals, position and individual conditions and finding situations. The obstacles faced in social interaction between the Samin community and the surrounding community are language differences that are difficult for the surrounding community to understand and the difference in values ??between the two social groups.